Critical care admissions in a cardiothoracic hospital: Mortality in patients aged over 80 years. (May 2015) - Quarterman, Clare; Kirmani, Bilal H; Al-Rawi, Omar
Background: Cardiac surgery is increasingly performed on patients aged 80 years and over. Previous studies have shown an associated longer length of hospital stay and higher morbidity and mortality. Our aim was to establish whether an increased mortality was demonstrated in patients aged over 80 undergoing surgery in our centre, and the impact of age upon critical care and hospital stay, and 30-day and 6-month survival. Methods: Over a 12-month period, 2042 critical care episodes were examined collectively and divided into those undergoing thoracic and cardiac surgery. Propensity matching of 216 patients who underwent cardiac surgery was performed for parameters including Acute Physiology And Chronic Health Evaluation (APACHE) II and Intensive Care National Audit and Research Centre score. Results: Of the admissions studied, 1784 were of patients under 80 years of age, and 258 over 80. Thirty-day mortality of those aged over 80 was significantly higher (8.9% vs. 3.8%, p < 0.0001), although the number of days of each level of organ support and total duration of critical care stay was not significantly different. Propensity matching of cardiac surgery patients indicated a longer length of hospital stay in those aged over 80, but no significant difference in length of critical care stay or mortality at six months. Conclusions: As previously demonstrated, we found an increased mortality in the older patient group. Following propensity matching, there was no significant difference in 30-day or 6-month mortality. Older patients must be fitter than their younger peers to compensate for the effects of age on APACHE II score. Even when this is taken into consideration, cardiothoracic operations appear to be safe in patients aged over 80.